Genetic Analysis of the T. aestivum/Ae. sharonensis Introgressive Lines of Common Wheat for Resistance to Powdery Mildew - Vdovychenko, Zh.V.; Antonyuk, M.Z.; Ternovskaya, T.K. (Цитология и генетика, 2005)
Results of investigation of peculiarities of common wheat hybridological analysis for a discrete character, resistance for powdery mildew, governed by the alien gene from Ae. sharonensis are present. Relation between genome structure of crossed introgressive lines and deviation of empirical ratios of segregation in F2 from theoretical, based on the assumption about monogenic inheritance of considered character is established. The approach to the quantitative count of influence of such connection on distortion of actual segregation in comparison with theoretically expected ratio is developed.